View of the new residence at Bonn of the Elector of Cologne in front of the Franciscan side - Leizelt, Balthasar Friedrich (engraver):::Creator:::::::::::: (2021)
Color vue d'optique engraving of the Elector's Palace in Bonn from the "Collection des Prospects" by Leizelt